Behavioral response to headache: a comparison between migraine and tension-type headache. - Martins, I (2014)
OBJECTIVE: To compare patients with migraine and tension-type headache in their behavior during the attacks and the maneuvers used to relieve the pain. BACKGROUND: Patients with headache often perform nonpharmacological measures to relieve the pain, but it is not known if these behaviors vary with the diagnosis, clinical features, and pathogenesis. METHODS: One hundred consecutive patients with either migraine (n = 72 ) or tension-type headache (n = 28) were questioned (including the use of a checklist) concerning their usual behavior during the attacks and nonpharmacological maneuvers performed to relieve the pain. The results of the two types of headache were compared. RESULTS: Patients with migraine tended to perform more maneuvers than individuals with tension-type headache (mean, 6.2 versus 3). These maneuvers included pressing and applying cold stimuli to the painful site, trying to sleep, changing posture, sitting or reclining in bed (using more pillows than usual to lay down), isolating themselves, using symptomatic medication, inducing vomiting, changing diet, and becoming immobile during the attacks. The only measure predominantly reported by patients with tension-type headache was scalp massage. However, the benefit derived from these measures was not significantly different between the two groups (except for a significantly better response to isolation, local pressure, local cold stimulation, and symptomatic medication in migraineurs). CONCLUSIONS: The behavior of patients during headache attacks varies with the diagnosis. Measures that do not always result in pain relief are performed to prevent its worsening or to improve associated symptoms. These behavioral differences may be due to the different pathogenesis of the attacks or to different styles of dealing with the pain. They can also aid the differential diagnosis between headaches in doubtful cases.